Air and seawater pollution and air-sea gas exchange of persistent toxic substances in the Aegean Sea: spatial trends of PAHs, PCBs, OCPs and PBDEs - Lammel, Gerhard; Audy, Ondřej; Besis, Athanasios; Efstathiou, Christos; Eleftheriadis, Kostas; Kohoutek, Jiři; Kukučka, Petr; Mulder, Marie D; Přibylová, Petra; Prokeš, Roman; Rusina, Tatsiana P; Samara, Constantini; et al. (Environmental science and pollution research international, 2015)
Near-ground air (26 substances) and surface seawater (55 substances) concentrations of persistent toxic substances (PTS) were determined in July 2012 in a coordinated and coherent way around the Aegean Sea based on passive air (10 sites in 5 areas) and water (4 sites in 2 areas) sampling. The direction of air-sea exchange was determined for 18 PTS. Identical samplers were deployed at all sites and were analysed at one laboratory. hexachlorobenzene (HCB), hexachlorocyclohexanes (HCHs) as well as dichlorodiphenyltrichloroethane (DDT) and its degradation products are evenly distributed in the air of the whole region. Air concentrations of p,p'-dichlorodiphenyldichloroethylene (p,p'-DDE) and o,p'-DDT and seawater concentrations of p,p'-DDE and p,p'-DDD were elevated in Thermaikos Gulf, northwestern Aegean Sea. The polychlorinated biphenyl (PCB) congener pattern in air is identical throughout the region, while polybrominated diphenylether (PBDE)patterns are obviously dissimilar between Greece and Turkey. Various pollutants, polycyclic aromatic hydrocarbons (PAHs), PCBs, DDE, and penta- and hexachlorobenzene are found close to phase equilibrium or net-volatilisational (upward flux), similarly at a remote site (on Crete) and in the more polluted Thermaikos Gulf. The results suggest that effective passive air sampling volumes may not be representative across sites when PAHs significantly partitioning to the particulate phase are included.
Keywords: Hexachlorobenzene; DDT; Seawater; dichlordifenyldichlorethylen; Polychlorinated Biphenyls; kvalita vody; chemické látky znečišťující vodu; Halogenated Diphenyl Ethers; halogenované difenylethery; Water Pollutants, Chemical; Greece; polychlorované bifenyly; Hexachlorocyclohexane; znečištění životního prostředí; Dichlorodiphenyl Dichloroethylene; Turkey; Environmental Pollution; hexachlorbenzen; Turecko; Air Pollutants; polycyklické aromatické uhlovodíky; Polycyclic Aromatic Hydrocarbons; Water Quality; mořská voda; látky znečišťující vzduch; hexachlorcyklohexan; Řecko